2018
DOI: 10.3390/f9030115
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Analysis of Pine Wilt Disease to Determine an Optimal Detection Index

Abstract: Bursaphelenchus xylophilus, the pine wood nematode (PWN) which causes pine wilt disease, is currently a serious problem in East Asia, including in Japan, Korea, and China. This paper investigates the hyperspectral analysis of pine wilt disease to determine the optimal detection indices for measuring changes in the spectral reflectance characteristics and leaf reflectance in the Pinus thunbergii (black pine) forest on Geoje Island, South Korea. In the present study, we collected the leaf reflectance spectra of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…In another attempt, an experiment ten vegetation indices formula to detect pine wilt disease on trees. They found that Equations 1 and 2 can detect infected trees earlier than other vegetation formulas (Kim et al, 2018). However, they also found that Equation 3 has better modeling than the others (Yuliantika et al, 2016).…”
Section: Vegetation Index Formulasmentioning
confidence: 98%
“…In another attempt, an experiment ten vegetation indices formula to detect pine wilt disease on trees. They found that Equations 1 and 2 can detect infected trees earlier than other vegetation formulas (Kim et al, 2018). However, they also found that Equation 3 has better modeling than the others (Yuliantika et al, 2016).…”
Section: Vegetation Index Formulasmentioning
confidence: 98%
“…For example, pine wilt disease was diagnosed using hyperspectral methods by Kim’s group. In their research, significant differences were observed in vegetation indices such as the normalized difference vegetation Index (NDVI), the green normalized difference vegetation index (GNDVI), the plant senescence reflectance index (PSRI), and the pigment specific normalized difference (PSND), beginning on 20 August 2012 [ 51 ]. Our group study the hyperspectral characteristic of healthy and withered masson pine, and Figure 2 shows the research results.…”
Section: Principles Of Monitoring Pwd With Hyperspectral Remote Sementioning
confidence: 99%
“…Similar to other xylophagous insects, M. alternatus mainly digests cellulose to obtain nutrients throughout the growth and development process, and this process requires the participation of cellulase for better digestion of the plant material [26,27]. Pine wilt disease has many characteristics, such as high mortality and fast onset, is widespread, and is called pine cancer by scholars [28][29][30]. PWD causes huge damage to the forestry economy [31,32].…”
Section: Introductionmentioning
confidence: 99%